BYPASSING DEFENSES THROUGH HUMAN MANIPULATION USING REVERSE TCP CONNECTIONS AND CUSTOM PAYLOADS: BYPASSING DEFENSES THROUGH HUMAN MANIPULATION USING REVERSE TCP CONNECTIONS AND CUSTOM PAYLOADS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This article explores a sophisticated cyberattack method that bypasses technical defenses by targeting human psychology. Instead of attacking systems directly, this approach uses the Social Engineering Toolkit (SET) to create convincing deceptive campaigns that persuade users to inadvertently initiate the attack themselves. A key technical element involves generating a custom Meterpreter payload, which is programmed to establish a Reverse TCP connection. This creates a stealthy command and control channel by having the compromised system "call back" to an attacker-controlled server, granting remote access. Our work demonstrates how this powerful fusion of human manipulation and technical execution poses a significant threat that often evades conventional, technology-focused security measures.